George Perry’s molluscan taxa and notes on the editions of his Conchology of 1811 - Petit, Richard E. (Zootaxa, 2003)
The molluscan taxa named by George Perry in his two publications, the Arcana; or the museum of natural history:, etc., published in 1810–1811, and the Conchology of 1811 are listed with notations on their current status, some figures being identified to the species level for the first time, some being placed in the synonymy of earlier names and others declared nomina dubia. Five species that are identified as previously unused senior subjective synonyms of names in current usage and one unused senior primary homonym are declared nomina oblita. Those declared herein to be nomina oblita are: Triplex cornuta Perry, 1811; Buccinella quadrata Perry, 1811; Cassis rotundata Perry, 1811; Aranea tentacula Perry, 1811; Buccinella tuberculata Perry, 1811; and Solen viride [sic; correctly viridis]. The names conserved are, respectively: Murex brevifrons Lamarck, 1822; Cancellaria spengleriana Deshayes, 1830; Cassis madagascariensis Lamarck, 1822; Murex cabritii Bernardi, 1859; Turbinella [now Vasum] globulus Lamarck, 1816; and Solen viridis Say, 1822.Three Perry species are shown to be senior synonyms of names in current use but do not qualify for nomen oblitum status under the Code. They are: Tellina aurea Perry, 1811; Triplex rosaria Perry, 1811; and Voluta pattersonia Perry, 1811. Junior subjective synonyms affected by these three are, respectively: Tellina vulsella Hanley, 1845; Chicoreus palmarosae (Lamarck, 1822); and Lyria nucleus (Lamarck, 1811). Type species designations for Perry’s genera are listed and type species are designated for Columna and Strigula. The treatment of Perry’s Conchology by other authors is discussed. Three distinct editions of the Conchology are identified. Perry’s Arcana is the subject of another paper now in preparation but its mollusks are treated herein.